Aplikasi Penghubung Guru dan Orang Tua: e-Counseling - Tyas Agustini; Abdi Wahab (Universitas Multimedia Nusantara, 2020)
SMP Negeri 89 is the first formal secondary education institution used for teaching and learning activities. There are many ways to improve students ' performance and discipline in one way by engaging teachers and parents to periodically monitor the activities of students in school and at home using a still-ongoing contact book. Manually causing constraints in the form of students to forge signatures of parents and books often left at home by students not brought back to school. The purpose of this research is to create a student activity Monitoring application in school or at home. In building this system the author uses Waterfall method. While for assisting in system analysis and design we use Unified Modeling Language (UML) and Waterfall method for developing the application. The Results from this research in SMP Negeri 89 Jakarta can be concluded that with Website-based Teacher and Parental Liaison Applications can facilitate teachers and parents in monitoring students.